A voltage-boosting strategy enabling a low-frequency, flexible electromagnetic wave absorption device - Lv, Hualiang (2020)
Nowadays, low-frequency electromagnetic interference (<2.0 GHz) remains a key core issue that plagues the effective attenuation performance of conventional absorption devices prepared via the component-morphology method (Strategy I). According to theoretical calculations, one fundamental solution is to develop a material that possesses a high ε' but lower ε″. Thus, it is attempted to control the dielectric values via applying an external electrical field, which inducts changes in the macrostructure toward a performance improvement (Strategy II). A sandwich-structured flexible electronic absorption device is designed using a carbon film electrode to conduct an external current. Simultaneously, an absorption layer that is highly responsive to an external voltage is selected via Strategy I. Relying on the synergistic effects from Strategies I and II, this device demonstrates an absorption value of more than 85% at 1.5-2.0 GHz with an applied voltage of 16 V while reducing the thickness to ≈5 mm. In addition, the device also shows a good absorption property at 25-150 °C. The method of utilizing an external voltage to break the intrinsic dielectric feature by modifying a traditional electronic absorption device is demonstrated for the first time and has great significance in solving the low-frequency electromagnetic interference issue.